2011
DOI: 10.5251/ajfn.2011.1.1.39.43
|View full text |Cite
|
Sign up to set email alerts
|

Effect of added brewers dry grain on the physico-chemical, microbial and sensory quality of wheat bread

Abstract: Bread samples were baked using wheat flour substituted with milled brewers' dry grain (BDG) at levels of 5, 10, 15 and 25%. The bread produced from wheat flour without BDG substitution served as control. The chemical composition, functional characteristics, microbial content and sensory attributes of the products were determined to ascertain their general acceptability. Results obtained showed an increase in the range of 8% for moisture, 3.5% for fat, 1.7% for Ash, 5.45% for crude fibre, 3.07% for protein and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 13 publications
1
25
0
1
Order By: Relevance
“…The highest moisture content (6.8%) was reported in the complementary food with 65% RTF, 20% MSF, and 15% PFP (FM1), and the lowest moisture content (5.2%) identified in the formulation with 65% RTF, 30% MSF, and 5% PFP (FM11). The moisture contents of the composite porridge increased with increase in RTF (55%–70%) and PFP (5%–15%) substitution by a range of 5.5%–6.6% and 5.2%–6.8%, consecutively (Elleuch et al., ; Haruna, Udobi, & Ndife, ). Study performed by Nair, Joglekar, and Sandhya () reported in contrast to this study, which showed that with increasing soy flour in rice‐based complementary food; the moisture content of the product was increased from 1.87 to 4.08.…”
Section: Resultsmentioning
confidence: 99%
“…The highest moisture content (6.8%) was reported in the complementary food with 65% RTF, 20% MSF, and 15% PFP (FM1), and the lowest moisture content (5.2%) identified in the formulation with 65% RTF, 30% MSF, and 5% PFP (FM11). The moisture contents of the composite porridge increased with increase in RTF (55%–70%) and PFP (5%–15%) substitution by a range of 5.5%–6.6% and 5.2%–6.8%, consecutively (Elleuch et al., ; Haruna, Udobi, & Ndife, ). Study performed by Nair, Joglekar, and Sandhya () reported in contrast to this study, which showed that with increasing soy flour in rice‐based complementary food; the moisture content of the product was increased from 1.87 to 4.08.…”
Section: Resultsmentioning
confidence: 99%
“…The emulsifying properties vary inversely with the insoluble protein fractions and polysaccharides (Chove, Grandison & Lewis, 2001;Haruna, Udobi & Ndife, 2011).…”
Section: Represents Thatmentioning
confidence: 99%
“…Different percent of BSG flour added to bakery products resulted in increase of total dietary fibre, total protein content, lipids, minerals and water holding capacity of the final product. The substitution of wheat flour with 5-20% BSG resulted in bread prototypes with enhance nutritional value and with pleasant flavour characteristics imparted by the specific volatile compounds [19,21,28,[41][42][43].…”
Section: Polysaccharidesmentioning
confidence: 99%